THE EFFECT OF HOLISTIC TEACHING MODEL AND STUDENTS’ INTROVERT-EXTROVERT PERSONALITIES ON STUDENTS’ ACHIEVEMENT IN WRITING ANALYTICAL EXPOSITION TEXT - Chandra Turnip .; I Wy Dirgeyasa; Anna Riana Tambunan (Universitas Negeri Medan, 2023)
This research was an experimental research. The objective of this experimental research was to investigate whether the achievement of writing analytical exposition text of introverted students was higher than extroverted students in the holistic learning model. The population of this research was the students in class XI both science and social class school academic year 2022/2023. The total number of population was 288 students and there were 36 students selected as sample of this research by applying teaching models. The research design was experimental research by using 2×2 factorial design. The questionnaires were conducted for classifying the students upon the introvert and extrovert personalities. Students’ achievement in analytical exposition text writing was measured by using writing test. The data were analyzed by applying two-way analysis of variance (ANOVA) at the level of significance α = 0.05. The result reveals that the achievement of writing analytical exposition text of introverted students was higher than extrovert students in the holistic learning model with total mean scores was 85.86 > 80.09.